A large-sized thermoelectric module composed of cement-based composite blocks for pavement energy harvesting and surface temperature reducing. (15th February 2023) - Wei, Jian; Zhou, Yuqi; Wang, Yuan; Miao, Zhuang; Guo, Yupeng; Zhang, Hao; Li, Xueting; Wang, Zhipeng; Shi, Zongmo
Abstract: Roads carry a lot of green and renewable energy. Thermoelectric cement as a green material can convert thermal energy to electrical power by using the temperature difference between the road surface and the underground. Cement-based materials can meet the needs for large-scale application in pavements because of their wide source, low cost, and good mechanical properties. Due to the preparation of large-size thermoelectric cement materials, the thermoelectric performance will be reduced, but the existing thermoelectric cement materials with excellent thermoelectric performance are small in size and they cannot be used for large-area applications. It is still a problem that thermoelectric properties of large-size thermoelectric cement-based composites prepared by the traditional pouring method are prone to dry shrinkage crack. Herein, to solve the problem of poor thermoelectric properties of large-sized thermoelectric cement materials. A thermoelectric cement block prepared by dry pressing is reported to be assembled into a large thermoelectric module of cement-based composite more suitable for pavement energy harvesting. The thermoelectric cement block is 50mm × 50mm × 20 mm, and the size of assembled into a large thermoelectric module is 300mm × 300mm × 35 mm. The addition of expanded graphite and metal oxides raised the average conductivity of the cement blocks to 0.63 S/cm and the average Seebeck coefficient to 20.79 μV/K, respectively. Tests have found that using a series connection of thermoelectric conversion modules can yield higher energy. Compared to other pavement thermoelectric generator (TEG) energy harvesting systems, the thermoelectric modules are less expensive and allow for large areas to be laid on the pavement. The module assembled using thermoelectric cement-based composite materials can generate 0.5 kW h of energy for 24 h on a road with a length of 1 km and a width of 10 m. Meanwhile, the thermoelectric module of cement-based composite has the ability to reduce the surface temperature and mitigate the urban heat island effect. The test results showed that it can reduce the temperature by 1°C–3°C. The results of this study provide a reference for future large scale practical applications of thermoelectric cement-based composites. Highlights: First assembly of thermoelectric devices with thermoelectric cement-based composites. The thermoelectric cement-based composite module has both the ability to convert, harvest energy and reduce pavement temperature.